Thin-skinned leaders: regime legitimation, protest issues, and repression in autocracies - Eda Keremoğlu; Sebastian Hellmeier; Nils B. Weidmann (Political Science Research and Methods, 2022)
The literature on autocracies has argued that repression of protest is either a result of the political environment in which protest occurs, or depends on particular characteristics of the protest events themselves. We argue that the interaction of both matters. Authoritarian regimes vary in how they legitimize their rule, and they should be particularly thin-skinned if protesters challenge the basis of their legitimacy. Using event-level data on mass mobilization in autocracies between 2003 and 2015, we use text classification methods to extract protest issues from newspaper reports. Our analysis shows that dictators are more likely to repress protest against incumbents when they claim legitimacy based on the person of the leader. Overall, our study shows that protest issues are not universal in triggering repression; rather, they need to be considered together with the political context in which they are raised.
doi:10.7910/DVN/AWQUHZ
Keywords: 300; protest; authoritarian regimes; repression; legitimation; demands